AdaptFlow: Protocol-based Medical Treatment Using Adaptive Workflows - Greiner, U.; Mueller, R.; Rahm, E.; Ramsch, J.; Heller, B.; Loeffler, M. (Methods of Information in Medicine, 2005)
Objectives: In many medical domains investigator-initiated clinical trials are used to introduce new treatments and hence act as implementations of guideline-based therapies. Trial protocols contain detailed instructions to conduct the therapy and additionally specify reactions to exceptional situations (for instance an infection or a toxicity). To increase quality in health care and raise the number of patients treated according to trial protocols, a consultation system is needed that supports the handling of the complex trial therapy processes efficiently. Our objective was to design and evaluate a consultation system that should 1) observe the status of the therapies currently being applied, 2) offer automatic recognition of exceptional situations and appropriate decision support and 3) provide an automatic adaptation of affected therapy processes to handle exceptional situations.Methods: We applied a hybrid approach that combines process support for the timely and efficient execution of the therapy processes as offered by workflow management systems with a knowledge and rule base and a mechanism for dynamic workflow adaptation to change running therapy processes if induced by changed patient condition.Results and Conclusions: This approach has been implemented in the AdaptFlow prototype. We performed several evaluation studies on the practicability of the approach and the usefulness of the system. These studies show that the AdaptFlow prototype offers adequate support for the execution of real-world investigator-initiated trial protocols and is able to handle a large number of exceptions.
Keywords: Clinical trials; clinical protocols; guidelines; event-oriented exception handling; adaptive workflow management